Loss of p16(INK4a) is associated with reduced patient survival in soft tissue tumours, and indicates a senescence barrier. Issue 7 (19th April 2014) - Knösel, Thomas; Altendorf-Hofmann, Annelore; Lindner, Lars; Issels, Rolf; Hermeking, Heiko; Schuebbe, Gesa; Gibis, Sebastian; Siemens, Helge; Kampmann, Eric; Kirchner, Thomas
Abstract : Aims: p16(INK4a) is an important factor in carcinogenesis, and its expression is linked to oncogene-induced senescence. Very recently it was shown that upregulation and downregulation of p16 indicates a senescence barrier in the serrated route of colorectal cancer. However, in soft tissue sarcoma (STS), the senescence mechanism is still not understood. In this study, we analysed a well characterised cohort of STS for p16(INK4a) expression and correlated the results with clinicopathological parameters including survival. Methods: Tissue microarrays (TMA) of 183 soft tissue and bone tumours were analysed immunohistochemically. Furthermore, mRNA expression of p16(INK4a) was evaluated in four sarcoma cell lines, and a demethylation test was performed by treatment with 5-aza-2′-deoxycytide. Results: On protein level, expression of p16(INK4a) was observed in undifferentiated pleomorphic sarcoma (UPS) in 69.1%, leiomyosarcoma in 85.7%, synovial sarcoma in 77.8%, liposarcoma in 88.9%, angiosarcoma in 60.9% and MPNST in 22.2%. Loss of p16(INK4a) was observed in high grade sarcomas and showed a significant correlation with reduced patient survival (p=0.032). On DNA level, one out of four sarcoma cell lines exhibited a methylated p16(INK4a) promoter analysed by methylation-specific PCR. p16(INK4a) mRNA and protein expression was restored after demethylation using 5-aza-2′-deoxycytide. Conclusions: Upregulation of p16(INK4a) might be associated with the induction of senescence and indicates a senescence barrier. Downregulation of p16(INK4a) is found in malignant progression, and is significantly correlated with reduced patient survival. Downregulation of p16(INK4a) may be explained by DNA-hypermethylation in sarcoma cells.